SWOT ANALYSIS OF THE DEVELOPMENT OF HALAL TOURISM IN IMPROVING THE ECONOMY OF THE COMMUNITY ISLAMIC ECONOMIC PERSPECTIVE - Heny Maulina Shodik; Hendri Hermawan Adinugraha; Razie Bin Nasarruddin (Imara: JURNAL RISET EKONOMI ISLAM, 2022)
ABSTRACTThis research aims to find out the analysis of Halal Tourism development in improving the economy of the islamic economic perspective community. This type of research is qualitative descriptive and literature studies using secondary data obtained from articles, books, the internet, previous studies and other reference sources relevant to the matter studied. Literature studies are used in the collection of research data. Understanding and analysis of library sources is used to produce studies on the topics discussed and draw research conclusions in order to get an explanation for the phenomenon being studied. The result of this study is that the development of Halal Tourism succeeded in improving the economy of the community. Halal Tourism in Indonesia has many opportunities if it is improved properly because Indonesia has a muslim-majority population.